Drawing from hats by noise-based logic. Issue 3 (4th May 2017) - Zhang, Bruce; Kish, Laszlo Bela; Granqvist, Claes-Göran
Abstract: We utilize the asymmetric random telegraph wave-based instantaneous noise-base logic scheme to represent the problem of drawing numbers from a hat, and we consider two identical hats with the first 2 N integer numbers. In the first problem, Alice secretly draws an arbitrary number from one of the hats, and Bob must find out which hat is missing a number. In the second problem, Alice removes a known number from one of the hats and another known number from the other hat, and Bob must identify these hats. We show that, when the preparation of the hats with the numbers is accounted for, the noise-based logic scheme always provides an exponential speed-up and/or it requires exponentially smaller computational complexity than deterministic alternatives. Both the stochasticity and the ability to superpose numbers are essential components of the exponential improvement.